2009
DOI: 10.1152/ajpheart.01051.2008
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced autophagy is mediated by oxidative signaling in cardiomyocytes and is associated with cytoprotection

Abstract: Bacterial endotoxin lipopolysaccharide (LPS) is responsible for the multiorgan dysfunction that characterizes septic shock and is causal in the myocardial depression that is a common feature of endotoxemia in patients. In this setting the myocardial dysfunction appears to be due, in part, to the production of proinflammatory cytokines. A line of evidence also indicates that LPS stimulates autophagy in cardiomyocytes. However, the signal transduction pathway leading to autophagy and its role in the heart are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
210
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(226 citation statements)
references
References 44 publications
14
210
2
Order By: Relevance
“…37 In addition, A. fumigatus-infected human monocytes and b-glucan-treated macrophages display autophagy responses mediated by SYKand NOX-dependent ROS production. 33,34,38 Ding et al 25 have also demonstrated that OxLDL-induced autophagy in endothelial cells is inhibited by the NOX inhibitor apocynin.…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, A. fumigatus-infected human monocytes and b-glucan-treated macrophages display autophagy responses mediated by SYKand NOX-dependent ROS production. 33,34,38 Ding et al 25 have also demonstrated that OxLDL-induced autophagy in endothelial cells is inhibited by the NOX inhibitor apocynin.…”
Section: Discussionmentioning
confidence: 99%
“…127 Lipopolysaccharide-induced autophagy was also shown to be paralleled by ROS formation and GSH depletion, which was prevented by NAC. 128 Treatment with gamma-glutamylcysteinyl ethyl ester, a precursor for de novo GSH formation, also prevents autophagy after traumatic brain injury. 129 Necrotic cell death is characterized by a gain in cell volume, swelling of organelles, plasma membrane rupture, and subsequent loss of intracellular contents.…”
Section: Figure 1 Apoptotic Signaling Pathways (See Text For Further mentioning
confidence: 99%
“…This method of assessing autophagic stimulation has been used before. [35][36][37] To make sure that the autophagosomes were being degraded in the lysosomes, we also measured autophagic flux by comparing relative increases in LC3-II/ LC3-I ratio under +BafA1 conditions in comparison to steadystate conditions. A larger difference in the LC3-II/LC3-I ratios under the two conditions indicated active clearance of autophagosomes by the lysosomes.…”
Section: Ama Increases Mitochondrial Omentioning
confidence: 99%
“…This method has been extensively used previously for measuring autophagic stimulation. [35][36][37] In addition, we measured autophagic flux by subtracting LC3-II/ LC3-I ratio under -BafA1 conditions from than of +BafA1 conditions.…”
Section: Flow Cytometric Determination Of Mitochondrial O 2 •− Generamentioning
confidence: 99%